The Future of Antiphospholipid Antibody Testing - de Groot, Philip G.; Urbanus, Rolf T. (Seminars in Thrombosis and Hemostasis, 2012)
The presence of antiphospholipid antibodies (aPL) is essential to diagnose the antiphospholipid syndrome (APS). Three assays are available to detect the presence of these autoantibodies, but all three assays suffer from several important drawbacks. First, the assays lack standardization because the results of the assay partially depend on the laboratory that performs the assay. Second, we do not know whether the assays detect the autoantibody population responsible for the clinical manifestations that characterize the syndrome. Finally, the assays do not predict the risk of recurrence. There is an absolute need for novel assays that generate prognostic information that can be used for a more tailored treatment of patients with APS. In 2011, important information became available on the protein against which the autoantibodies are directed, β2-glycoprotein I (β2GPI). Based on the progress we have made in our understanding of the physiology of β2GPI, it should be possible to design assays that can better predict the consequences of the presence of aPL in the circulation.
Keywords: lupus anticoagulant; antiphospholipid antibodies; β2-glycoprotein I; anticardiolipin antibodies